(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article reflects on the recent reform that has lifted, under German law, the prohibition for doctors to provide information on the abortion procedures they perform. In particular, it is argued that this testifies to a fundamental change in the social and legal perception of voluntary termination of pregnancy and thus represents only a first step towards a radical paradigm shift in the legal regulation of abortion procedures in Germany. The article shows how the ban on advertising and information was an essential pillar of the legal and political compromise on abortion and analyses the implications of its lifting in the light of the constitutional principle of state neutrality.